2005
DOI: 10.2308/iace.2005.20.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evidence on the Association between Critical Thinking and Performance in Principles of Accounting

Abstract: This study tests whether critical-thinking skills can help explain the cross-sectional variation in student performance in principles of accounting. Prior research has used such measures as academic aptitude and demographic factors to explain performance in the principles of accounting class. We argue that success in principles of accounting also requires critical-thinking skills. We measured critical-thinking skills by using a holistic scoring process to evaluate student essays. Our results show that even aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 6 publications
3
43
0
2
Order By: Relevance
“…Moreover, most cited literature appears to indicate a significantly positive effect of the identified dimensions found in entrepreneurial leadership (i.e., responsibility, accountability, analytical thinking, and emotional intelligence) on an enterprise's performance cf. [34][35][36]38,43,44,[53][54][55]67,68]. At the same time, the existing literature suggests a significantly positive relationship between enterprise performance and sustainability [74,75].…”
Section: The Mediating Effect Of Micro-enterprise Performancementioning
confidence: 69%
See 1 more Smart Citation
“…Moreover, most cited literature appears to indicate a significantly positive effect of the identified dimensions found in entrepreneurial leadership (i.e., responsibility, accountability, analytical thinking, and emotional intelligence) on an enterprise's performance cf. [34][35][36]38,43,44,[53][54][55]67,68]. At the same time, the existing literature suggests a significantly positive relationship between enterprise performance and sustainability [74,75].…”
Section: The Mediating Effect Of Micro-enterprise Performancementioning
confidence: 69%
“…Meanwhile, Ibdah [54] claimed that analytical thinking, as a means of confronting problems and dealing with both internal and external changes related to varied business activities, boosts the performance level of firms. Additionally, Kealey, Holland, and Watson [55] empirically proved that analytical thinking skills contribute significantly towards performance among students. Hence, considering both the theory and existing literature, the following hypothesis is proposed.…”
Section: Analytical Thinking and Micro-enterprise Performancementioning
confidence: 99%
“…Riley, Cadotte, Bonney, & MacGuire, 2013). These are definitely not new to accounting educators, what is rather new and goes beyond the utilization of rubrics is the increased focus on authentic assessment as well as the need to assess skills such as knowledge transfer, problem-solving, and critical thinking across the entire curriculum (Kealey, Holland, & Watson, 2005).…”
Section: How the Use Of Rubrics Can Enhance Students' Learningmentioning
confidence: 99%
“…Ghanizadeh and Mirzaee (2012) confirmed that EFL learners' critical thinking can predict about 28% of their language achievement. Throughout history, a range of other studies have demonstrated the association of critical thinking with students' academic success as well (e.g., Lee & Loughran, 2000;Kealey, Holland, & Watson, 2005).…”
Section: International Journal Of Research Studies In Language Learnimentioning
confidence: 99%